Sistem Pendukung Keputusan Penerimaan Karyawan Mengunakan Metode Simple Additive Weighting (Saw) Berbasis Web - Pertiwi, Monik; Sarjono, Sarjono (LPPM Universitas Dinamika Bangsa, 2022)
The process of recruiting new employees at PT. BPD Jambi is currently still using the manual method where PT. BPD Jambi provides an assessment for the recruitment of prospective employees which is still done manually so that all data on the selection of prospective new employees do not have a fixed weight, and mistakes often occur so that there are prospective employees who do not meet the standards of passing the selection process. The purpose of this study is to analyze the current system in employee recruitment at PT BPD Jambi and design a decision support system for employee recruitment at PT BPD Jambi with the simple additive weighting (SAW) method. Analysis and design of the employee acceptance decision support system using this web-based simple additive weigthing (SAW) method using object-based modeling techniques to describe system analysis and design, namely in the form of use case diagrams, activity diagrams, and class diagrams. The output of this research is in the form of a prototype system design. Analysis and Design of a Decision Support System for Employee Admissions Using a web-based simple additive weigthing (SAW) method.